The impact of internal solitary waves on deep-sea benthic organisms on the continental slope of the northern South China Sea - Feng, Xuezhi; Wang, Linsen; Ji, Chunsheng; Wang, Hui; Zhu, Chaoqi; Jia, Yonggang (Frontiers in Marine Science, 2023)
Internal solitary waves (ISWs) exert a significant influence on the deep-sea floor, yet little research has been conducted on their impact on benthic organisms. The objective of this study was to investigate the propagation characteristics of ISWs on the Shenhu continental slope in the northern South China Sea, as well as their mechanisms of influence on benthic activity. In-situ observation was performed at the head of the Shenhu Canyon (water depth 655m) to determine the physical characteristics of ISWs and the changes in benthic organisms. The study revealed that the abundance and density of benthic organisms were positively correlated with the time and intensity of ISWs. The abundance of benthic organisms affected by ISWs is 3-5 times that without ISWs, and the density of benthic organisms is 3-9 times. The impact induced by ISWs, including resuspension of bottom sediments, formation of marine snow, changes in the bottom boundary layer environment, and vertical transfer of seawater environmental factors, played a crucial role in the impact on benthic activity. To our limited knowledge, this is the first in-situ long-term observation study on the effects of ISWs on deep-sea benthic organisms on the continental slope of the northern South China Sea deeper than 600m, providing new insights for exploring the environmental impact of ISWs on the deep-sea bottom boundary layer.